Composition and Dissolution of a Migratory, Weathered Coal Tar Creosote DNAPL - Scherr, Kerstin E.; Vasilieva, Viktoriya; Lantschbauer, Wolfgang; Nahold, Manfred (Frontiers in Environmental Science, 2016)
Opaque, viscous tars derived from the carbonization of fossile carbon feedstocks, such coal tars and creosote, are long-term sources of groundwater contamination, predominantly with poly- and heterocyclic aromatic hydrocarbons (PAH). The dissolution, ageing and migratory behavior of dense, non aqueous phase liquid (DNAPL) coal tar blobs and pools forming at the aquitard is not sufficiently understood to estimate the risk and adequately design groundwater treatment measures at a contaminated site. In this study, we investigate the composition and dissolution of a migrated, aged creosote DNAPL and corresponding experimental and groundwater profiles using comprehensive two-dimensional gas chromatography (GCxGC-MS). GC-FID unresolved compounds were attributed to methylated homocyclic species using GCxGC-MS in the Methylanthracene weight range. Equilibrium concentrations were estimated using Raoult’s law, assuming non-ideal behavior. Low molecular weight compounds were found to be prevalent even after decades of weathering, with Naphthalene (8% by mass) representing the most abundant identified compound, contrary to the expected preferential depletion of hydrophilic compounds. Morevoer, dimethylnaphthalenes were relatively more abundant in the aqueous boundary layer than in the DNAPL. DNAPL migration over 400m with the groundwater flow effected lower viscosity and specific gravity of the migrated phase body in a superposition of weathering, transport and aquifer chromatography effects. Based on a decomposition of analysed and estimated constituents using the group contribution approach, reference DNAPL values for activity coefficients γi were used to model aqueous solubilities for selected compounds. Anthracene was close to its theoretical precipitation limit in the bulk DNAPL. While laboratory and modelled DNAPL dissolution behavior agree well, field data imply the presence of specific interfacial in situ processes significantly impacting dissolution processes. Based on aqueous GCxGC-MS profiles over the DNAPL, a hypothetical interfacial in situ film was calculated to be composed primarily of Phenanthrene, with minor contribution by Naphthalene, possibly forming a viscous barrier for the dissolution of lower molecular weight PAH. The main advances and gaps in electron donor DNAPL understanding are discussed regarding our conception of weathered, migrating hydrophobic DNAPL bodies in the aquifer of historic contaminated sites for the adequate treatment of contaminated water.